2021
DOI: 10.20944/preprints202105.0246.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Identification of Root Rot Disease by Using Hyperspectral Reflectance: The Case of Pathosystem Grapevine/Armillaria

Abstract: The Armillaria genus represents one of the most common causes of chronic root rot disease in woody plants. The disease damage prompt assessment is crucial for pest management. However, the disease detection current methods are limited at the field scale. Therefore, an alternative approach that can enhance or supplement traditional techniques is needed. In this study, we investigated the potential of hyperspectral methods to identify the changes between fungi-infected and uninfected plants of Vitis vinifera in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, the medicinal parts of most medicinal plants, like ginsengs, are roots, whose hyperspectral reflectance data cannot be collected directly and non-constructively. Calamita et al (2021) found significant differences in the nearinfrared spectral region of leaves between healthy and root-rot grape plants by the naive bayes algorithm, which showed 90% accuracy in the identification of healthy and diseased plants, indicating the possibility for the diagnosis of root rot in plants by applying hyperspectral reflectance from leaves. However, such detection method is rarely mentioned by previous researchers and has not been reported in medicinal plants.…”
Section: Discussionmentioning
confidence: 92%
“…However, the medicinal parts of most medicinal plants, like ginsengs, are roots, whose hyperspectral reflectance data cannot be collected directly and non-constructively. Calamita et al (2021) found significant differences in the nearinfrared spectral region of leaves between healthy and root-rot grape plants by the naive bayes algorithm, which showed 90% accuracy in the identification of healthy and diseased plants, indicating the possibility for the diagnosis of root rot in plants by applying hyperspectral reflectance from leaves. However, such detection method is rarely mentioned by previous researchers and has not been reported in medicinal plants.…”
Section: Discussionmentioning
confidence: 92%
“…Although the initial symptoms of root rot are not obvious, subtle changes in tissue metabolic pathways occur when plant tissues are attacked by the causal fungus. The NIR broadspectrum method can rapidly identify this nuanced difference to diagnose the health status of the plant, making it effective for the early detection of plant root rot (Calamita et al, 2021). However, little research has been conducted on the differential changes in tissue metabolic pathways following infection by pathogenic fungi in C. oleifera, hindering the promotion and application of this technology in monitoring fungal diseases in this plant.…”
Section: Establishing An Accurate Monitoring and Forecasting Systemmentioning
confidence: 99%